Immediate outcomes of AVNeo in combination with coronary artery bypass grafting - V. V. Bazylev; A. B. Voevodin; V. A. Karnakhin; A. A. Martynov; N. V. Zhukov (Российский кардиологический журнал)
Aim. To evaluate immediate outcomes of the Ozaki procedure in patients with coronary artery bypass grafting (CABG).Material and methods. This retrospective study included 416 patients operated on at the Federal Center of Cardiovascular Surgery (Penza). The patients were divided into two groups. The first group included 139 patients who underwent the AVNeo procedure in combination with CABG. The second group included 277 patients who underwent a single AVNeo procedure.Results. The median time of cardiopulmonary bypass and myocardial ischemia in the AVNeo+CABG group was 146 (134-165) and 115 (104-125), respectively, while in the AVNeo group — 117 (102-136) and 96 (82-109), respectively. The mean aortic valve pressure gradient immediately after surgery in the AVNeo+CABG group was 5,9±3,3, while in the AVNeo group — 6,4±3,1. Mortality in the AVNeo+CABG group was 2,8% (n=4), while in the AVNeo group — 0,3% (n=1). Inhospital survival in the AVNeo+CABG group was 97,1%, while in the AVNeo group — 99,6%. In the AVNeo+CABG group, there were following death causes: perioperative myocardial infarction (n=2), pneumonia (n=1), multiple organ failure (n=1). In the AVNeo group, the cause of the only fatal outcome was multiple organ failure. Only one predictor of inhospital mortality was identified — resternotomy for bleeding. In the case of resternotomy, inhospital death risk increases by 1,3 times for each day of the postoperative period. Cardiopulmonary bypass time, myocardial infarction, and operation duration do not affect mortality. The combination of AVNeo with CABG also does not affect inhospital mortality (p=0,1).Conclusion. The combination of the AVNeo procedure with CABG is an effective and safe procedure in the immediate period.